Hiding elephants in mouseholes: influence of gatekeeping by social media platforms on social media activity / Jaspal Kaur Sadhu Singh - Sadhu Singh, Jaspal Kaur (2014)
The power of media has shifted from corporations that owned traditional mainstream media to new media entities namely Internet content providers such as social media platforms taking on the role played by traditional mainstream media in terms of being tools for freedoms, the Fourth Estate and the platform for democratic discourse. This is phenomenon is seen in terms of how citizens are engaging with each other and the world in the realm of socio-political discourse and that these social media platforms have emerged as tools of freedom of expression and speech, particularly in the context of citizen journalists on the Internet. However, information that is posted on these platforms is subjected to a filtering process influenced by ownership and internal policies which has the effect of censoring information, news and commentary. In terms of ownership, traditional media in democracies has been nationally subjected to a requirement of diversity - from the viewpoint of ownership, content, politics and culture - imposed by laws and regulatory bodies. The article enquires into the need to subject social media platforms owners to such standards. In terms of internal policies imposed on users, by reference to case studies, the article explores the impact of these internal policies on information posted on social media platforms and whether these policies impinge on socio-political discourse produced by citizen journalists on the Internet. Reference will be made to political theories namely the deliberative democracy theory, as well as media-related theories such as Habermas‟s Public Theory and Marketplace of Ideas Theory that bears heavily on the role of media entities. The policies reviewed are seen in the global context with references to several national legislative frameworks.